Expression and Characterization of Recombinant Murine Factor VIII - Doering, Christopher B.; Parker, Ernest T.; Healey, John F.; Craddock, Heather N.; Barrow, Rachel T.; Lollar, Pete (Thrombosis and Haemostasis, 2002)
Hemophilia A is the inherited bleeding disorder that results from mutation of blood coagulation factor VIII (fVIII). Described here is the generation of a regulated expression system producing recombinant murine fVIII. Murine B-domainless fVIII was expressed at a peak level of 4 units/106 cells/24 h in serum-free media. Subsequently, a two-step purification procedure resulted in 5,300-fold enrichment and a 70% yield. Highly purified recombinant murine fVIII had a specific coagulant activity of 660 units per nanomole. It underwent proteolytic processing by thrombin to yield an activated heterotrimer that demonstrated significantly greater stability than activated human fVIII. Recombinant murine fVIII was utilized to generate an anti-fVIII polyclonal antibody. Intravenous injection of recombinant murine fVIII into hemophilia A mice failed to induce a significant anti-fVIII immune response using a schedule that yielded high titer inhibitory antibodies to human fVIII. This may provide an important model for the study of immune tolerance to fVIII.
Keywords: Recombinant; factor VIII; mouse; doxycycline-controlled expression